2017
DOI: 10.7224/1537-2073.2016-068
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord as an Adjunct to Brain Magnetic Resonance Imaging in Defining “No Evidence of Disease Activity” in Multiple Sclerosis

Abstract: CME/CNE Information Activity Available Online: To access the article, post-test, and evaluation online, go to http://www.cmscscholar.org. Target Audience: The target audience for this activity is physicians, physician assistants, nursing professionals, and other health-care providers involved in the management of patients with multiple sclerosis (MS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Our spinal cord imaging may have been limited by lower sensitivity with the reliance on available routine clinical images. With higher resolution research-dedicated protocols and other more sensitive sequences, such as short time inversion recovery (STIR), we may have been able to capture more lesions [ 37 , 38 ]. In addition, the MRI scans were performed at 1.5T; however, with the growing use of 3T scanners for routine MS care and 7T scanners for research investigations, and their potentially higher lesion sensitivity in the brain and spinal cord [ 15 , 39 ], it would be of interest to extend our results to higher field strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Our spinal cord imaging may have been limited by lower sensitivity with the reliance on available routine clinical images. With higher resolution research-dedicated protocols and other more sensitive sequences, such as short time inversion recovery (STIR), we may have been able to capture more lesions [ 37 , 38 ]. In addition, the MRI scans were performed at 1.5T; however, with the growing use of 3T scanners for routine MS care and 7T scanners for research investigations, and their potentially higher lesion sensitivity in the brain and spinal cord [ 15 , 39 ], it would be of interest to extend our results to higher field strengths.…”
Section: Discussionmentioning
confidence: 99%
“…16 SC-MRI monitoring in pwMS on first-line DMT also led to a modest but statistically significant 7.8% decrease in the proportion of pwMS with NEDA in another recent study. 18 However, Tummala et al 17 showed a low diagnostic yield of 3T SC-MRI in the 1-year evaluation of NEDA with 39/61 (63.9%) pwMS achieving NEDA by brain MRI; only one showed disease activity on SC-MRI that was also clinically symptomatic, resulting in no or disability worsening over median follow-up intervals ranging from 14 to 42 months. 14,15,32 These results further underscore the notion that the utility of SC-MRI for disease monitoring may be limited, even when using NEDA, the "highest bar" of treatment outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…16 SC-MRI monitoring in pwMS on first-line DMT also led to a modest but statistically significant 7.8% decrease in the proportion of pwMS with NEDA in another recent study. 18 However, Tummala et al 17 showed a low diagnostic yield of 3T SC-MRI in the 1-year evaluation of NEDA with 39/61 (63.9%) pwMS achieving NEDA by brain MRI; only one showed disease activity on SC-MRI that was also clinically symptomatic, resulting in no failure of NEDA based on SC-MRI alone. Although we were not able to evaluate NEDA in our study due to the lack of availability of EDSS scores that were done concurrently with MRIs, we were still able to evaluate those who were clinically stable with respect to relapses and MRI disease activity, and the relative contribution of adding SC-MRI to brain MRI in evaluating NEDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, routine clinical MRIs may not have offered the same surveillance as do more frequent MRIs performed in clinical trials. Additionally, not all patients underwent routine spinal cord surveillance, although this is low yield in monitoring for NEDA 24. While our study utilised medical record documentation of fatigue complaints, a comparison of DTI changes with formal assessments of fatigue and cognition would be beneficial in future studies.…”
Section: Discussionmentioning
confidence: 99%